Residential exposure to municipal solid waste incinerators and health effects: a systematic review with meta-analysis - Isabella Bottini; Simona Vecchi; Manuela De Sario; Lisa Bauleo; Alessandro Trentalange; Paola Michelozzi; Carla Ancona (BMC Public Health)
Abstract Background Municipal solid waste incinerators (MSWIs) are widely used for waste management. However, the health effects of their emissions remain uncertain, needing further investigation and monitoring of the potential risks associated with such exposure. The aim of this study is to update and synthesize evidence on the health effects of residential exposure to MSWIs. Methods A systematic review with meta-analysis was conducted following PRISMA guidelines. The systematic search in MEDLINE, EMBASE, and Web of Science (April 2025), using specific search strategies, identified observational studies reporting quantitative estimates on the association between long term residential exposure to MSWIs and health outcomes. Study quality was assessed using the Navigation Guide tool. A narrative synthesis was conducted for all outcomes. When possible, a random-effects meta-analysis was performed and Higgins I2 was used to summarize heterogeneity. For the overall body of evidence, heatmaps were used to visually represent the direction of the associations (positive, negative or lack of association) stratified by study quality. Results Out of 3,273 records identified, 51 studies were included. The most frequently investigated outcomes were congenital anomalies, pregnancy outcomes, cardiovascular and respiratory diseases, and cancers. The narrative synthesis suggests a weak association for hospitalizations due to cardiovascular and respiratory diseases in high-quality studies and a potential increased risk for non-Hodgkin lymphoma, based on low-quality evidence. The meta-analysis confirms a slight increased risk for respiratory diseases (HR 1.02; 95% CI 0.94–1.11), particularly for COPD (HR 1.08; 95% CI 0.82–1.41) and asthma (HR 1.02; 95% CI 1.00–1.05). Moderate heterogeneity was observed for most outcomes (I2 = 30%-60%). Conclusions This review highlights the current uncertainty surrounding the long-term health effects of MSWI exposure. While a slight indication of increased risk emerged for cardiovascular and respiratory hospitalizations, and a weak association with non-Hodgkin’s lymphoma was observed, overall evidence remains weak. Methodological limitations, heterogeneity across studies, and low exposure levels complicate risk assessment and comparability. Standardized, high-quality research is needed to clarify these associations and support evidence-based public health decisions and transparent communication with affected communities. Trial registration The protocol of this review was registered in PROSPERO on 02/06/2024 (CRD42024550168).